The alley as a studio: one-way street (Revista Apotheke, 2025)
This visual essay presents, in a poetic way, a series of paintings and procedural registers made by the Brazilian state of Minas Gerais artist Camila Lacerda (between the years of 2014 and 2025) that has the alley as its main theme. On the next pages, the alley will be analyzed from different perspectives: as a transitory space, as a habitable space and as an expanded studio. This work was divided into two parts. In the first part, the artist and researcher Vanessa Deister provides a brief critical essay on the topic. In the second part, Lacerda builds a visual narrative blending unpublished works, with reproductions of paintings already known to the audience and photographic records of encounters and poetic situations obtained during the creative process of these works. It is emphasized that the conception of this visual essay results from exchanges of artistic-collaborative experiences in the context of college teaching and learning, as the authors are professors in the same undergraduate program in visual arts, at the Universidade Estadual de Maringá (UEM).
Keywords: contemporary painting; visual essay; creative processes